2011
DOI: 10.1242/jeb.055897
|View full text |Cite
|
Sign up to set email alerts
|

Microstome–macrostome transformation in the polymorphic ciliateTetrahymena voraxleads to mechanosensitivity associated with prey-capture behaviour

Abstract: SUMMARYCiliates feed by phagocytosis. Some ciliate species, such as Tetrahymena vorax, are polymorphic, a strategy that provides more flexible food utilization. Cells of the microstomal morph of T. vorax feed on bacteria, organic particles and organic solutes in a non-selective manner, whereas macrostome cells are predators that consume specific prey ciliates. In the present study, we investigated a possible correlation between phagocytosis and mechanosensitivity in macrostome T. vorax. Microstome cells seem t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Transformation from microstome to macrostome T. vorax cells is associated with dramatic changes in cell size and shape, and gaining of novel mechanosensitivity that contributes to the different behaviour of the two morphs (Grønlien et al. ). Still, the present report shows that the general electrical membrane properties are strikingly similar in microstome and macrostome cells (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation from microstome to macrostome T. vorax cells is associated with dramatic changes in cell size and shape, and gaining of novel mechanosensitivity that contributes to the different behaviour of the two morphs (Grønlien et al. ). Still, the present report shows that the general electrical membrane properties are strikingly similar in microstome and macrostome cells (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that microstome T. vorax cells seem to be insensitive to mechanical stimulation, whereas macrostome cells depolarize in response to mechanical stimulation of the anterior part of the cell (Grønlien et al. ). The difference in mechanosensitivity of the two morphs correlates with the swimming behaviour when hitting an obstacle, and the mechanosensitivity of macrostome cells may also be associated with their prey‐capture behaviour.…”
mentioning
confidence: 99%
“…Reaction norms allow organisms to quickly adapt to the changes in the environment and efficiently maximize their fitness under the given circumstances without changes in the genome. A well-known example of such phenotypic plasticity is described in the protist Tetrahymena vorax, which is able to switch between two distinct morphotypesmacrostome and microstome-in response to environmental changes, such as the relative abundance of bacteria versus other protists [142,143]. Interestingly, when a macrostome or microstome undergoes cell division it can either maintain its corresponding morphology or change to a distinct morphotype depending on resource abundance.…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…may be expected to utilize similar conserved sensory mechanisms, it is likely that they implement them in different ways due to their different morphological and ecological characteristics. Nevertheless, it is known that ionotropic mechanisms -those governed by voltage-, chemo-, or mechano-sensitive ion channels -are important in regulating the behaviors of ciliates (Preston and Van Houten, 1987;Shiono and Naitoh, 1997;Grønlien et al, 2011). For example, ionotropic mechanisms are known to be important in sensory processes that relate to prey capture in ciliates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ionotropic mechanisms are known to be important in sensory processes that relate to prey capture in ciliates. Contact of the freshwater ciliate Tetrahymena vorax with prey cells elicits ciliary reversal and backward swimming, which are regulated by transient depolarizations (Grønlien et al, 2011). Ionotropic mechanisms may also be important in regulating predator evasion behaviors.…”
Section: Introductionmentioning
confidence: 99%